Antioxidant, antidiabetic and molecular docking studies of D-pinitol isolated from Cleistopholis patens (Benth) leaf extract - Olukayode Solomon Ajayi; Emmanuel Gabriel Fakola; Fiyinfoluwa Funmibi Olubiyo; Olaoye Solomon Balogun; Idowu Julius Olawuni; Tawakalit Omolara Kelani (Discover Chemistry)
Abstract Cleistopholis patens is a medicinal plant with secondary metabolites that possess diverse biological activities that are beneficial to humans. It is used in the management of diabetes as well as treatment of jaundice, infective hepatitis, stomach disorders among others. Synthetic drugs used for treatment of diabetes mellitus often have side effects, hence, the search for natural sources of antidiabetic drug. This study set out to evaluate the phytochemicals, antioxidant capacity effects of the solvent fractions and enzyme inhibition of the isolated compound from Cleistopholis patens (Benth) leaf. The extracts were further evaluated for the total phenolic (TPC) and flavonoid content (TFC). The aqueous methanol fraction was subjected to column chromatography over stationary phases such as silica gel and sephadex LH-20, the isolated compound 1; (D-pinitol) were characterized using IR and NMR spectroscopy techniques. The 2,2-Diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging, Ferric reducing antioxidant power (FRAP) and Total antioxidant capacity (TAC) assays were used to evaluate antioxidant potentials of the extract and solvent fractions. Furthermore, in silico molecular docking and ADMET analysis were carried out on the only isolated compound (D-pinitol) with other standard antidiabetic drugs to predict the its pharmacokinetic indicators and toxicity. The results exhibited that the ethyl acetate fraction has higher levels of total phenolics (129.16 ± 5.59 mg GAE/g) and flavonoids (209.84 ± 2.82 mg QUE/g) compared with the crude methanol extract (73.61 ± 2.43 mg GAE/g and 76.99 ± 9.99 mg QUE/g) respectively. The antioxidant activity studies revealed that ethyl acetate fraction demonstrated higher radical scavenging in DPPH (IC50 of 0.08 ± 0.02 mg/mL) and TAC (222.28 ± 8.71 mg AAE/g) respectively. While for reducing abilities (FRAP), ethyl acetate fraction has also the highest activity (50.22 ± 3.28 mg AAE/g) than the crude methanol extract (30.61 ± 1.74 mg AAE/g). D-pinitol exhibited α-amylase and α-glucosidase inhibitory activity with IC50 values of 59.61 ± 0.71 µg/mL and 124.83 ± 0.06 µg/mL respectively, compared with acarbose (standard drug) with 16.32 ± 0.01 µg/mL and 73.67 ± 0.02 µg/mL. Therefore, this study investigates the antioxidant potential, in vitro α-amylase and α-glucosidase inhibitory activities of Cleistopholis patens leaf extract and isolated compound, D-Pinitol.